Evaluation of Association Between Hyperlipidemia and Heart Rate Variability in Subjects Without Apparent Cardiovascular Disease - (:unkn) unknown (My University, 2015)
Giriş: Literatürde hiperlipidemi ve kalp hızı değişkenliği (KHD) ilişkisiyle ilgili sınırlı sayıda veri mevcuttur. Çalışmamızın amacı aşikâr kardiyovasküler veya sistemik hastalığı olmayan bireylerin kayıtlarını retrospektif olarak inceleyerek KHD ve hiperlipidemi arasındaki ilişkiyi araştırmaktır. Hastalar ve Yöntem: Ocak 2012 ve Mayıs 2013 tarihleri arasında kliniğimizde 24 saatlik Holter tetkiki yapılan tüm hastaların medikal kayıtları incelendi. Sistemik veya kardiyovasküler hastalığı olmadığına karar verilen kişilerin verileri analizde kullanıldı. Bulgular: Toplam 37 kişinin verisi kullanıldı. Yirmi kişinin hiperlipidemik (10 erkek, yaş: 44.5 ± 11.1) oldu- ğu saptanırken 17 kişinin normal lipit profi line sahip olduğu izlendi (5 erkek, yaş: 33.4 ± 10.6; cinsiyet için p= 0.18 ve yaş için p= 0.004). Hiperlipidemik hasta grubunda normal lipit profi li grubuna göre çoğu KHD parametresinin anlamlı derecede deprese olduğu izlendi ancak aritmi prevalansları arasında fark saptanmadı. Lineer regresyon analizinde serum trigliserid düzeyinin RMSSD, PNN50 ve LF/HF oranı ile bağımsız olarak ilişkili olduğu görüldü (sıra ile beta= -0.40, p= 0.02; beta= -0.41, p= 0.012 ve beta= -0.31, p= 0.05). Sonuç: Retrospektif çalışmamız sonucunda hiperlipidemisi olan grupta normal lipit profi li olan kişilere göre kalp hızı değişkenliğinin anlamlı derecede deprese olduğu gözlendi. Gözlemlerimiz sonucunda özellikle hipertrigliseridemisi olan hiperlipidemik kişilerin daha yüksek kardiyak sempatik aktivite gösterdikleri ve bu durumun artmış kardiyovasküler morbidite ve mortalite ile ilişkili olabileceği düşünülebilir.

Introduction: There is limited data in the literature regarding the association between hyperlipidemia and heart rate variability (HRV). The aim of the present study is to investigate the association between HRV and hyperlipidemia by retrospectively evaluating the recordings of subjects free of any apparent cardiovascular or systemic disease. Patients and Methods: Medical records of patients to whom 24 hour-Holter recording was performed in our clinic between January 2012 and May 2013 were retrospectively examined. Data of subjects who were determined to be free of any cardiovascular or systemic disease were used in the analysis. Results: Data of 37 subjects were used. There were 20 subjects with hyperlipidemia (10 male, age: 44.5 ± 11.1 years) and 17 subjects with normal lipid profi le (5 male, age: 33.4 ± 10.6 years; p= 0.18 for gender and p=0.004 for age). Majority of HRV parameters were found to be signifi cantly depressed in group with hyperlipidemia; however, there were no signifi cant difference between groups regarding prevalence of arrhythmias. Out of components of the lipid profi le, linear regression analysis revealed serum triglyceride level to be independently associated variable with RMSSD, PNN50 and LF/HF ratio (in respective order; beta= -0.40, p= 0.02; beta= -0.41, p= 0.012 and beta= -0.31, p= 0.05). Conclusion: Subjects with hyperlipidemia were observed to have signifi cantly depressed HRV compared to subjects with normal lipid profi le in our retrospective study. Based on our observations, it may be suggested that patients with hyperlipidemia, in particular with hypertriglyceridemia display higher subtle cardiac sympathetic activity which may be associated with increased cardiovascular morbidity and mortality.
Bilinen Kardiyovasküler Hastalığı Olmayan Kimselerde Hiperlipidemi ve Kalp Hızı Değişkenliği Arasındaki İlişkinin Araştırılması
Keywords: Kalp ve Kalp Damar Sistemi